The gut microbiome and metabolome in children with a first febrile urinary tract infection: a pilot study - Piteková, Barbora; Hric, Ivan; Zieg, Jakub; Baranovičová, Eva; Konopásek, Patrik; Gécz, Jakub; Planet, Paul J; Bielik, Viktor (Pediatric nephrology (Berlin, Germany), 2025)
BACKGROUND: Urinary tract infection (UTI) is a common bacterial infection in the pediatric population. Febrile urinary tract infection (fUTI) can lead to severe complications such as urosepsis as well as kidney scarring, chronic kidney disease, and systemic hypertension. Recent research supports the hypothesis that dysbiosis of the microbiome may play a role in the pathogenesis and development of fUTI in infants. Our main aim was to compare the shift in gut microbiota composition between children with the first fUTI and controls. METHODS: We conducted an observational study with 17 children with the first fUTI compared to 18 healthy controls. We performed analysis of the gastrointestinal microbiome and measurements of metabolites in stool and urine. RESULTS: In the gut microbiome, we found significant differences with lower α-diversity the Shannon index) and significantly lower relative abundance of probiogenic bacteria (short-chain fatty acids (SCFA)) in children with the first episode of fUTI before the start of antibiotic therapy. Furthermore, our findings confirm that the length of breastfeeding has significant influence on gut microbiota composition, reducing pathogenic bacteria and enhancing beneficial taxa. Shannon diversity, duration of breastfeeding, and specific taxa, particularly Faecalibacterium and Escherichia, emerged as strong predictors linked to the development of fUTI. CONCLUSIONS: This study demonstrates that gut microbiome changes are associated with the onset of fUTI in children. Machine learning models identified Shannon index, specific bacterial taxa, and breastfeeding as strong predictors of fUTI. The study highlighted the potential role of the gut microbiome in preventing fUTI.
Keywords: mužské pohlaví; infekce močového ústrojí; Breast Feeding; Male; Pilot Projects; feces; Feces; Dysbiosis; Humans; Female; kojenec; kojení; lidé; Fever; Kidney; Anti-Bacterial Agents; ženské pohlaví; Infant; metabolom; Urinary Tract Infections; horečka; střevní mikroflóra; studie případů a kontrol; Case-Control Studies; dítě; Child; Metabolome; Pyelonephritis; SCFA; pilotní projekty; Pediatric; Child, Preschool; antibakteriální látky; Gut microbiota; předškolní dítě; dysbióza; Gastrointestinal Microbiome